Foreign direct investment and firm innovation in selected sub-Saharan African Countries - Joseph Dery Nyeadi; Charles Komla Delali Adjasi (Cogent Business & Management, 2020)
The impact of innovation on every economy cannot be overemphasized. Hence, this study investigates empirically the impact of inward FDI on host firms' innovation in Nigeria and South Africa using the World Bank Enterprise Survey dataset (WBES). In examining this relationship between FDI and firm innovation, two robust instrumental variable estimation techniques (two-stage least squares and limited information maximum likelihood) were employed so as to account for any endogeneity problems. The study establishes that while FDI positively influences firm innovation in Nigeria, it does not have any impact on firm innovation in South Africa. This study thus presents evidence that context is very crucial in the investigation of the link between FDI and innovation in Sub-Saharan Africa. It is thus recommended that FDI attraction into Africa should be selectively done with more focus on inflows from more advanced and innovative economies.
Keywords: 650; FDI; process innovation; product innovation; South Africa; Nigeria andinstrumental variable